O aborto em pauta: a atuação de movimentos pró-vida no Brasil contemporâneo - Manduca, Vinicius (2021)
This thesis presents the results of research for the conclusion of a doctorate on the political strategies of action of pro-life movements, opponents of the decriminalization of abortion before and during the government of Jair Messias Bolsonaro. Elected religious representatives and civil society entities organize themselves into movements exerting political pressure, seeking to make the parliament legislate in favor of their beliefs and convictions, contrary to other social segments. It is in this scenario that pro-life movements are projected. If before the 2018 elections, marked by an institutional political rise of conservatism, they acted mostly against the agenda, they gave a new tone to these movements, as they were now members of the executive power, personalized in the figure of the Minister for Women, Family and Rights Humans, Damares Alves. He was selected for the study National Citizenship Movement for Life – Brasil Sem Aborto. The study was carried out through systematic analysis of campaign materials, news and official documents from selected entities, in addition to an interview with the minister.